The double challenge of resistant hypertension and chronic kidney disease - Rossignol, Patrick; Massy, Ziad A.; Azizi, Michel; Bakris, George; Ritz, Eberhard; Covic, Adrian; Goldsmith, David; Heine, Gunnar H.; Jager, Kitty J.; Kanbay, Mehmet; Mallamaci, Francesca; Ortiz, Alberto; et al. (The lancet, 2015)
Resistant hypertension is defined as blood pressure above goal despite adherence to a combination of at least three optimally dosed antihypertensive medications, one of which is a diuretic. Chronic kidney disease is the most frequent of several patient factors or comorbidities associated with resistant hypertension. The prevalence of resistant hypertension is increased in patients with chronic kidney disease, while chronic kidney disease is associated with an impaired prognosis in patients with resistant hypertension. Recommended low-salt diet and triple antihypertensive drug regimens that include a diuretic, should be complemented by the sequential addition of other antihypertensive drugs. New therapeutic innovations for resistant hypertension, such as renal denervation and carotid barostimulation, are under investigation especially in patients with advanced chronic kidney disease. We discuss resistant hypertension in chronic kidney disease stages 3-5 (ie, patients with an estimated glomerular filtration rate below 60 mL/min per 1·73 m(2) and not on dialysis), in terms of worldwide epidemiology, outcomes, causes and pathophysiology, evidence-based treatment, and a call for action.